IgG4‐related disease manifesting the gastric wall thickening. Issue 1 (24th November 2015) - Kawano, Hiroo; Ishii, Aya; Kimura, Tokuhiro; Takahashi, Tsuyoshi; Hironaka, Hideharu; Kawano, Michitaka; Yamaguchi, Michiya; Oishi, Keiji; Kubo, Makoto; Matsui, Shoko; Notohara, Kenji; Ikeda, Eiji
Abstract : IgG4‐related disease (IgG4‐RD) is a recently designated disease entity and its full picture has not yet been elucidated. Here, we report an unusual case of a patient with gastric wall thickening secondary to IgG4‐RD. A 68‐year‐old male visited our hospital with itchy skin lesions and an episode of organizing pneumonia. On the suspicion of malignancy‐associated skin lesions, computed tomography (CT) was performed. The CT revealed prominent thickening of the gastric wall. Due to the possibility of malignancy, the patient underwent distal gastrectomy. Histopathological examination showed fibrosis of the submucosa and prominent thickening of the muscularis propria. Most of infiltrating cells were IgG4‐positive plasma cells. Post‐operative blood test revealed significantly high serum levels of total IgG and IgG4. Based on these histological features, the patient was given a definitive diagnosis of IgG4‐RD. Further accumulation of cases like the present case that develop IgG4‐RD with rare manifestations would lead to the elucidation of pathogenesis.